Factors influencing the rate of diffusion of innovative products. - Lee, Lai Juan. (2008)
The objective of this paper is to study factors affecting the rate of diffusion of innovative products where we studied the adoption of camera-integrated mobile phone. We used the Roger's diffusion theory as background and analyzed the factors relating to Marketing Mix, 4Ps to extend Roger's research.